Figurative Language in Lana Del Rey’s and Taylor Swift’s Song Lyrics - Isabela Aileen (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study analyzes figurative language in two song albums: Born to Die (2012) by Lana Del Rey and reputation (2017) by Taylor Swift. Using Perrine’s (2017) theoretical framework, this qualitative research examines figurative devices found in selected song lyrics. The data consist of lyrics from both albums. The findings reveal that both artists use various types of figurative language, including simile, metaphor, personification, metonymy, symbol, allegory, paradox, overstatement, understatement, and irony. Lana Del Rey frequently uses symbolic and emotional imagery and often combines multiple figurative devices within a single line, while Taylor Swift emphasizes narrative clarity and emotional contrast. Apostrophe appears only in Lana Del Rey’s lyrics. The study also identifies mixed figurative types, with seven combinations in Lana Del Rey’s songs and six in Taylor Swift’s. Overall, figurative language in both albums strengthens themes, emotions, and storytelling.